2012
DOI: 10.1093/ckj/sfs011
|View full text |Cite
|
Sign up to set email alerts
|

Long-term haemodialysis survival

Abstract: Haemodialysis (HD) treatment for end-stage renal disease bears a poor prognosis. We present a case of a patient who, apart from two transplant periods lasting 8 months in all, was treated with conventional in-centre HD three times a week and who survived for 41 years. Patients should be aware that there is no theoretical upper limit for patient survival on HD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…The longevity of HD patients in general can vary as some receive renal transplants or change dialysis methods. Allowing for this, their survival is typically longer than patients with lung cancer; in one study, survival was reported at 72% after 10 years and has been documented as upwards of 35 years .…”
Section: Discussionmentioning
confidence: 99%
“…The longevity of HD patients in general can vary as some receive renal transplants or change dialysis methods. Allowing for this, their survival is typically longer than patients with lung cancer; in one study, survival was reported at 72% after 10 years and has been documented as upwards of 35 years .…”
Section: Discussionmentioning
confidence: 99%
“…At least in settings where dialysis efficiency has been a key goal in recent decades, the "skeleton man" is now seldom encountered in dialysis wards, except in cases in which diffuse and severe vascular disease is accompanied by a reduction in food intake, often in a context of cognitive impairment in elderly patients [71][72][73][74]. Another exception is patients with a very long dialysis follow-up, whose clinical situation is often dominated by diffuse precocious bone or vascular disease [75][76][77][78][79][80] (Figure 1).…”
Section: From the "Skeleton Man" To The Obese Sarcopenic Patientmentioning
confidence: 99%
“…Dialysis treatment is continuously improving, ensuring better tolerance and overall higher survival of a population that is steadily getting older and more complicated. Although the therapeutic armamentarium is now far more varied than in the past, virtually all the long-term problems related to uremia and its treatments are still unsolved: cardiovascular diseases are still the main cause of death in a context of accelerated vascular ageing; vascular access malfunction still makes it often difficult to optimize treatment; Chronic Kidney Disease related Mineral and Bone Disorder (CKD-MBD) remains one of the plagues of long-term dialysis treatment [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%